Influence of Depth of Hypnosis on Pupillary Reactivity to a Standardized Tetanic Stimulus in Patients Under Propofol-Remifentanil Target–Controlled Infusion: A Crossover Randomized Pilot Study. (January 2018) - Sabourdin, Nada; Peretout, Jean-Baptiste; Khalil, Eliane; Guye, Marie-Laurence; Louvet, Nicolas; Constant, Isabelle
Abstract : BACKGROUND: Pupillometry allows the measurement of pupillary diameter variations in response to nociceptive stimuli. This technique has been used to monitor the balance between analgesia and nociception. Under general anesthesia, the amplitude of pupillary dilation is related to the amount of administered opioids. The objective of this study was to determine whether at a constant infusion rate of opioids, the pupillary response was influenced by depth of hypnosis assessed by the bispectral index (BIS). METHODS: Twelve patients (14–20 years) anesthetized for orthopedic surgery were included. Under propofol-remifentanil target–controlled infusion, remifentanil effect site target concentration was fixed at 1 ng/mL. Two measures of pupillary reflex dilation were performed on each patient in a randomized order: one at BIS 55 and one at BIS 25. These levels of BIS were obtained by adjusting propofol target concentration and maintained for 10 minutes before each measure. For each measure, we applied a standardized tetanic stimulation on the patient's forearm (60 mA, 100 Hz, 5 seconds). All measures were performed before the beginning of surgery. RESULTS: Pupillary dilation was significantly greater at BIS 55 than at BIS 25: 32.1% ± 5.3% vs 10.4% ± 2.5% (mean difference estimate [95% confidence interval]: 21.8% [12.9–30.6], P < .001), without carryover effect ( P = .30) nor period effect ( P = .52). Hemodynamic parameters and BIS were not modified by the stimulation. CONCLUSIONS: In patients receiving a constant infusion of remifentanil at a target concentration of 1 ng/mL, pupillary dilation after a standardized tetanic stimulation was influenced by depth of hypnosis assessed by the BIS. Abstract : Published ahead of print January 19, 2017.